Characterization and Dynamics of Repeatomes in Closely Related Species of Hieracium (Asteraceae) and Their Synthetic and Apomictic Hybrids - Zagorski, Danijela; Hartmann, Matthias; Bertrand, Yann J. K.; Paštová, Ladislava; Slavíková, Renata; Josefiová, Jiřina; Fehrer, Judith (Frontiers in Plant Science, 2020)
The repetitive content of the plant genome (repeatome) often represents its largest fraction and is frequently correlated with its size. Transposable elements (TEs), the main component of the repeatome, are an important driver in the genome diversification due to their fast-evolving nature. Hybridization and polyploidization events are hypothesized to induce massive bursts of TEs resulting, among other effects, in an increase of copy number and genome size. Little is known about the repeatome dynamics following hybridization and polyploidization in plants that reproduce by apomixis (asexual reproduction via seeds). To address this, we analyzed the repeatomes of two diploid parental species, Hieracium intybaceum and H. prenanthoides (sexual), their diploid F1 synthetic and their natural triploid hybrids (H. pallidiflorum and H. picroides, apomictic). Using low-coverage next-generation sequencing (NGS) and a graph-based clustering approach, we detected high overall similarity across all major repeatome categories between the parental species, despite their large phylogenetic distance. Medium and highly abundant repetitive elements comprise ~70% of Hieracium genomes; most prevalent were Ty3/Gypsy chromovirus Tekay and Ty1/Copia Maximus-SIRE elements. No TE bursts were detected, neither in synthetic nor in natural hybrids, as TE abundance generally followed theoretical expectations based on parental genome dosage. Slight over- and under-representation of TE cluster abundances reflected individual differences in genome size. However, in comparative analyses, apomicts displayed an overabundance of pararetrovirus clusters not observed in synthetic hybrids. Substantial deviations were detected in rDNAs and satellite repeats, but these patterns were sample specific. rDNA and satellite repeats (three of them were newly developed as cytogenetic markers) were localized on chromosomes by fluorescence in situ hybridization (FISH). In a few cases, low-abundant repeats (5S rDNA and certain satellites) showed some discrepancy between NGS data and FISH results, which is due partly to the bias of low-coverage sequencing and partly to low amounts of the satellite repeats or their sequence divergence. Overall, satellite DNA (including rDNA) was markedly affected by hybridization, but independent of the ploidy or reproductive mode of the progeny, whereas bursts of TEs did not play an important role in the evolutionary history of Hieracium.